Gentrification and Displacement: The Forced Relocation of Public Housing Tenants in Inner-Sydney - Morris, Alan.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book examines the forced displacement of public housing residents in Sydney's Millers Point and The Rocks communities. It considers the strategies deployed by the government to pressure tenants to move, and the social and personal impacts of the displacement on the residents themselves. Drawing on in-depth interviews with tenants alongside government and media communications, the Millers Point case study offers a penetrating and moving analysis of gentrification and displacement in one of Australia's oldest and more unique working class and public housing neighbourhoods. Gentrification and Displacement advances work in urban studies by charting trends in urban renewal and displacement, furthering our understanding of public housing, gentrification and the effects of forced relocation on vulnerable urban communities.
Chapter 1. Introduction and setting -- Chapter 2. A brief history -- Chapter 3. A "unique community" -- Chapter 4. The build-up to the displacement -- Chapter 5. The impact of the displacement announcement -- Chapter 6. Why tenants moved, part 1 -- Chapter 7. Why tenants moved, part 2 -- Chapter 8. The impact of the move -- Chapter 9. Conclusions - where to from here? -- Appendix A. Profile of interviewees -- Appendix B. Where tenants were moved to -- Appendix C. Methodology.
Keywords: Sociology, Urban; Human geography; Urban Sociology; Human Geography